Chronic stress and age‐related pattern of blood pressure: A cross‐sectional study in rural China. Issue 1 (22nd June 2020) - Yazawa, Aki; Inoue, Yosuke; Tu, Raoping; Yamamoto, Taro; Watanabe, Chiho; Kawachi, Ichiro
Abstract: Objective: Chronic stress is a risk factor for hypertension in adults. However, there is conflicting evidence for older adults. We hypothesized that age‐related arterial stiffening, which leads to a lower blood pressure (especially diastolic blood pressure [DBP]), is more pronounced among older adults with high vs low stress. The objectives of this study were (a) to investigate age‐related trends in systolic and DBPs among adults in rural Fujian, China, and (b) to examine differences in age‐related blood pressure trends according to levels of stress by using Epstein‐Barr virus (EBV) antibody titer as a marker of chronic stress status. Methods: We collected cross‐sectional data from 764 rural community‐dwelling adults in rural Fujian, China (mean age = 59.4). Participants were categorized into high and low stress groups by median split of EBV antibody titer. A least‐squares regression analysis was used to investigate the association between age and blood pressures. Results: We observed an inverted U‐shaped association between age and DBP, while there was a linear association between age and systolic blood pressure in the overall sample. When stratified by stress, the inverted U‐shaped associations with age (both systolic and DBPs) were seen only among those with high stress; DBP peaked at the age of ~68 years, and the declining trend later in life was more clearly observed among those with high chronic stress. Discussion: Decrease of DBP was more pronounced among older adults with high vs low chronic stress in rural China.